(untitled) (International Journal of Engineering and Computer Science, 2016)
In wireless communication, the connections will be either unstable or dynamic. Hence the connections will be easily disturbed by the interrupts like noise. Now-a-days mobile networks provide the internet connections with expensive cost. Cellular networks suffer from offloading and overloading problem due to the explosive growth of mobile users in moving vehicles. WIFI technology is used to provide the efficient internet connectivity for the moving vehicles. WIFI technology has some advantages compared with the cellular networks, such as, low cost and high peak throughput. To avoid the offloading problem and delays in the internet access over moving vehicles, the access point diversity technique is used. For example multiple access points can be fixed in the road side. When the client can enters that environment, it can communicate with the group of access point through the up link. Each access point may have different ranges. So, when the client is moving from one access point to another access point, the delays may be occurred due to the hand off technique. Hence the virtual access point is created in order to avoid the delays. Virtual access point is the one, in which all the access points are configured with the same MAC and IP address. If the transmission is succeed access point send the information to the client through the multi cast communication. Then the access points dynamically follow the client and deliver the packets.